EFFECTS OF FLEXIBLE SUPPORTING STRUCTURE AND WIND LOADS ON YAW BEARING’S LOAD DISTRIBUTION - DU Jing; GONG JiaYi; YANG XianGang (Jixie qiangdu)
In order to investigate the effects of finite element modeling parameters,such as the stiffness of flexible supporting structure and wind loads applying on tower,on the yaw bearing load distribution,a FE simulation model of MW-class wind turbine yaw bearing system was developed using Hypermesh and Ansys. Subsequently,the Hertz contact model was adopted to validate the nonlinear contact of the ball to raceway. Finally,the effects of varying stiffness of the restraint system,tower wind load and other factors on the performance of the bearing load distribution were discussed. The results show that with the increase of the length of the tower FE model,which means the decrease of restraint stiffness,load of the ball decreases and the theoretic fatigue life increases,and it tends to be constant when the modeling length of the tower is larger than 3 times of the yaw bearing’s diameter. Furthermore,considering wind loads applying on the tower,load on balls of the windward side decreases,while those of the leeward side increases,and the theoretic fatigue life increases.